2014
DOI: 10.1111/acer.12577
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol Exposure Impairs Executive Function in Mice into Adulthood

Abstract: Background Despite evidence that prenatal alcohol exposure (PAE) can lead to a wide range of impairments in cognitive, social and emotional behaviors, drinking during pregnancy remains common. Although there is a general understanding that high levels of drinking during pregnancy are unsafe, conflicting evidence regarding the impact of low intake may account for the persistence of this behavior. Methods In order to investigate the effects of PAE on learning and executive control we utilized a voluntary parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
(81 reference statements)
6
57
0
Order By: Relevance
“…All operant behavior was conducted in a chamber measuring 21.6 x 17.8 x 12.7 cm (model # ENV-307W, Med Associates, St. Albans, VT), housed within a sound- and light- attenuating box (Med Associates, St. Albans, VT) as previously described (Marquardt et al, 2014). The standard grid floor of the chamber was covered with a solid acrylic plate to facilitate ambulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All operant behavior was conducted in a chamber measuring 21.6 x 17.8 x 12.7 cm (model # ENV-307W, Med Associates, St. Albans, VT), housed within a sound- and light- attenuating box (Med Associates, St. Albans, VT) as previously described (Marquardt et al, 2014). The standard grid floor of the chamber was covered with a solid acrylic plate to facilitate ambulation.…”
Section: Methodsmentioning
confidence: 99%
“…Touch-screen automated paradigms have become increasingly utilized to screen rodent models of numerous neuropsychiatric disorders (Marquardt et al, 2014, Yang et al, 2015, Copping et al, 2016, Leach et al, 2016) as these paradigms closely model tools used in the clinical assessment and may increase translational potential of preclinical studies (Mar et al, 2013, Talpos and Steckler, 2013, Hvoslef-Eide et al, 2016). While previous studies have demonstrated that lesion and/or inactivation of the region is sufficient to disrupt visual touch-screen reversal, it has not yet been demonstrated that the rodent OFC mediates reversal of complex visual stimuli in an analogous manner to those seen in primates using visual stimuli (Clarke et al, 2008), or to more species-specific stimuli such as spatial, olfactory or tactile stimuli in rodents (Hamilton and Brigman, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Visual sensory processing was not directly tested in this study, so it remains possible that alterations to visual acuity influenced percent omissions in ethanol-treated mice. Evidence against this interpretation includes the lack of treatment effects on percent accuracy below the 8 s stimulus duration or on correct response latency at any stimulus duration, and a published finding that developmental ethanol exposure does not affect learning of a visual discrimination task (Marquardt et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…It is well established that in spatial-reversal tasks (Y-maze, T-maze, MWM), rodents show impairment on reversal, even when there are no effects on acquisition of the initial spatial discrimination in both high- and moderate-dose paradigms (An & Zhang, 2013; Hamilton et al, 2014; Lee & Rabe, 1999; Riley, Lochry, Shapiro, & Baldwin, 1979; Thomas, Garrison, & O’Neill, 2004; Wainwright et al, 1990). Recently we have shown that reversal impairments are not confined to spatial learning, as a moderate exposure during the first two trimesters impairs reversal of visual stimuli in a touch-screen operant task (Marquadt, Sigdel, Caldwell, & Brigman, 2014). …”
Section: Learning Memory and Executive Control (Cognitive)mentioning
confidence: 99%